Vaccine manufacturing in Islamic perspective - Mel, Maizirwan; Ja'afar, Ja'afar Nuhu (IIUM Press, 2009)
Recent progress in biotechnology and basic immunology is leading to the development of a wide range of new vaccines raising possibilities for the prevention of infectious diseases. In addition, improvement to already licensed vaccine is also being considered leading to new products as well as the introduction of a new type of adjuvant. However, the complexity and novelty of these products presents scientific and regulatory challenges, as criteria for their safety, potency and quality assessment may not always exist. Another important challenge being debated is of the production of halal vaccine that can be used by Muslims all over the world, which must come from allowable or permitted sources. The guiding principle of Good Manufacturing Practice (GMP) is that quality is built into a product, and not just tested. Therefore, the assurance is that the product not only meets the final specifications, but that it has been made by the same procedures under the same conditions each and every time it is made. Islamic validation is the part of GMP that ensures the facility systems, equipments processes and test procedures are in control and therefore consistently produce a quality vaccine product. Therefore in this paper the halal of biological manufacturing will be highlighted by discussing the good manufacturing processes and validation regulations of the vaccine.